Acute Basal Ganglia Enlargement with Obsessive-Compulsive Disorder, Tics, and Strep Infection - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
A 12-year-old boy with an acute exacerbation of obsessive-compulsive disorder (OCD) symptoms and tics following a Group A B-hemolytic streptococcal (GABHS) throat infection is reported from the National Institute of Mental Health, Bethesda, MD.